Cross-border clusters as the form of transplantation of institutions into economic area of postmodernity - Kovalenko, S.I. (Економічні інновації, 2015)
Досліджено механізм трансплантації інститутів мережевої економіки як необхідний чинник зростання конкурентоспроможності єврорегіонів в умовах євроінтеграції України. На основі інституційного підходу обґрунтовано, що постіндустріальна економіка еволюціонувала в систему взаємодіючих інститутів формують новий економічний простір постмодерну в транскордонному вимірі. Розглянуто сутність та внутрішні взаємозв'язки транскордонного кластеру як чинника зростання конкурентоспроможності єврорегіону. The mechanism of transplantation of network economics institutions is studied as the necessary growth factor of competitive capacity of the European regions in terms of European integration. By means of institutional approach it is justified that postindustrial economics evolved into the system of interlocking institutions, forming a new economic area of postmodernity in cross-border dimension, in which such virtual resources of development are necessary as: information, innovations, ways of communication, knowledge and other institutions of postindustrial society. The subject and internal connections of cross-border cluster is investigated as the growth factor of competitive capacity of the European region in terms of tightening the integration process and the necessity of enhancement of the role of peripheral regions economics under cross-border cooperation.

It is concluded that a new postmodern reality lies in the combination of postindustrial production with the network construction of economic area, involving transplantation of the institutions by means of self-organization of hybrid network clusters on both sides of the border that becomes the factor of integration and free circulation of the funds in the European regions.